Cancer of esophagus and GE junction– a long-term follow-up results - Thakur, Binay; Yonghui, Di; Devkota, Mukti; Baral, Paribartan; Shrestha, Sudhir; Upreti, Janaki; Kandel, Nirmala (Journal of Society of Surgeons of Nepal, 2016)
Background:  Esophageal and GE Junction malignancies are diagnosed late and the long-term outcome is still suboptimal. We present our experience.Methods: 421 patients with mean age of 57.6 years with cancer of esophagus and GE Junction were evaluated with physical examination, CT chest and abdomen, gastroduodenoscopy and bronchoscopy. 254 (60.4%) patients underwent surgical treatment only and 167 (39.6%) underwent multimodality treatment. 295 patients underwent transthoracic approach, 88 – transhiatal approach and 58 patients underwent – abdominal approach only.Results: Upper, middle, GEJ type – I, GEJ type – II, GEJ type – III tumors were present in 5.7, 28.5, 36.8 and 1.9% cases, respectively. Anastomosis was placed at neck in 73.2% and in chest in 26.8% cases. Final stages were 0 (0.2%), Ia (0.5%), Ib (1.9%), IIa (10%), IIb (8.8%), IIIa (15.7%), IIIb (14.3%), IIIc (41.6%) and IV (7.1%). R0 resection was achieved in 91.5% cases. Postoperative mortality, recurrent laryngeal nerve injury, anastomotic leak and pneumonia were observed in 4.8%, 5.7%, 11.6% and 22.1%, respectively. Median overall survival was 28 months with 5-year overall survival of 21%. A subgroup of 70 patients (16.6%) who were subjected to preoperative chemoradiation followed by surgery showed response in 64.3% cases with a median and 5-year survival of 49 months and 30% in responders, and 15 months and 15% in non-responders.Conclusion: Patients presented mostly in stage III (78.7%), therefore a multimodality approach should be considered as a standard practice in Nepalese context in order to achieve better survival results.